Perceptions of the gap between theory and practice in the preparation of English language teachers at the Lesotho College of Education - Molete, Bakae (Rhodes University, Faculty of Education, Department of Education, 2008)
The distinction between theory and practice can be traced back to Aristotle (384-322 B.C). Theory has been seen as the preserve of the academician who, through research, produces knowledge for the practitioner to use in his/her practice. This research sets out to investigate perceptions of the respondents with regard to the extent to which theory is applicable in practice. It does this in the context of teacher training at the Lesotho College of Education, (LCE), a teacher training college in Lesotho. In this research project; a case study of 5 students from the LCE who had been on teaching practice, their mentor teachers on teaching practice, and a college lecturer who had observed said students on teaching practice was used. Data was collected by means of focus group interviews and semi-structured interviews. Relevant documents in the form of classroom observation forms were also used. The findings from the data analysis revealed that students on teaching practice had, to a great extent, had difficulties in applying what they had learned at the college when they got to teaching practice. Difficulties were mainly experienced in the areas of classroom and time management as well as in the application of the teaching methods learned at the college. This research takes a closer look at these difficulties. It investigates their probable causes and, finally, suggests ways of responding to them.
Keywords: Lesotho College of Education; Education -- Research -- Lesotho; Teachers -- Training of -- Lesotho; Student teaching -- Lesotho; English language -- Study and teaching -- Lesotho; Observation (Educational method); English teachers -- Training of -- Lesotho